Altered JS‐2 expression in colorectal cancers and its clinical pathological relevance - Alfred King-Yin Lam; Vinod Gopalan; Mohammad Reza Nassiri; Kais Kasim; Jayampathy Dissanayake; Johnny Chuek-On Tang; Robert Anthony Smith (Molecular Oncology)
Abstract JS‐2 is a novel gene located at 5p15.2 and originally detected in primary oesophageal cancer. There is no study on the role of JS‐2 in colorectal cancer. The aim of this study is to determine the gene copy number and expression of JS‐2 in a large cohort of patients with colorectal tumours and correlate these to the clinicopathological features of the cancer patients. We evaluated the DNA copy number and mRNA expression of JS‐2 in 176 colorectal tissues (116 adenocarcinomas, 30 adenomas and 30 non‐neoplastic tissues) using real‐time polymerase chain reaction. JS‐2 expression was also evaluated in two colorectal cancer cell lines and a benign colorectal cell line. JS‐2 amplification was noted in 35% of the colorectal adenocarcinomas. Significant differences in relative expression levels for JS‐2 mRNA between different colorectal tissues were noted (p = 0.05). Distal colorectal adenocarcinoma had significantly higher copy number than proximal adenocarcinoma (p = 0.005). The relative expression level of JS‐2 was different between colonic and rectal adenocarcinoma (p = 0.007). Mucinous adenocarcinoma showed higher JS‐2 expression than non‐mucinous adenocarcinoma (p = 0.02). Early T‐stage cancers appear to have higher JS‐2 copy number and lower expression of JS‐2 mRNA than later stage cancers (p = 0.001 and 0.03 respectively). Colorectal cancer cell lines showed lower expression of JS‐2 than the benign colorectal cell line. JS‐2 copy number change and expression were shown for the first time to be altered in the carcinogenesis of colorectal cancer. In addition, genetic alteration of JS‐2 was found to be related to location, pathological subtypes and staging of colorectal cancer.